2014
DOI: 10.3389/fnhum.2014.00672
|View full text |Cite
|
Sign up to set email alerts
|

Familiarity is not notoriety: phenomenological accounts of face recognition

Abstract: From a phenomenological perspective, faces are perceived differently from objects as their perception always involves the possibility of a relational engagement (Bredlau, 2011). This is especially true for familiar faces, i.e., faces of people with a history of real relational engagements. Similarly, valence of emotional expressions assumes a key role, as they define the sense and direction of this engagement. Following these premises, the aim of the present study is to demonstrate that face recognition is fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…First, we considered the level of familiarity, since previous studies have shown that we respond faster to familiar faces compared with unfamiliar faces (Burton et al, 2011), and thus we could expect that the overall effect observed could be larger when considering self-face versus unfamiliar faces. Second, we considered the effect of identity, since differences have been found in terms of behavioral performance (Liccione et al, 2014), as well as physiological (Guerra, Sanchez-Adam, Anllo-Vento, Ramirez, & Vila, 2012a;Guerra et al, 2012b;Vico, Guerra, Robles, Vila, & Anllo-Vento, 2010), and neuronal (Gobbini & Haxby, 2007;Gobbini et al, 2004) processes involved in the processing of famous (people we have seen only through the media) and familiar (people we have personally encountered in life) faces. These differences may be explained by the amount and type of experience individuals have with the familiar and famous (Burton et al, 2011) as well as other affective aspects (Guerra et al, 2012a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we considered the level of familiarity, since previous studies have shown that we respond faster to familiar faces compared with unfamiliar faces (Burton et al, 2011), and thus we could expect that the overall effect observed could be larger when considering self-face versus unfamiliar faces. Second, we considered the effect of identity, since differences have been found in terms of behavioral performance (Liccione et al, 2014), as well as physiological (Guerra, Sanchez-Adam, Anllo-Vento, Ramirez, & Vila, 2012a;Guerra et al, 2012b;Vico, Guerra, Robles, Vila, & Anllo-Vento, 2010), and neuronal (Gobbini & Haxby, 2007;Gobbini et al, 2004) processes involved in the processing of famous (people we have seen only through the media) and familiar (people we have personally encountered in life) faces. These differences may be explained by the amount and type of experience individuals have with the familiar and famous (Burton et al, 2011) as well as other affective aspects (Guerra et al, 2012a).…”
Section: Discussionmentioning
confidence: 99%
“…These differences may be explained by the amount and type of experience individuals have with the familiar and famous (Burton et al, 2011) as well as other affective aspects (Guerra et al, 2012a). As suggested by Liccione et al (2014), Baffective and emotional aspects related to personal narratives with others seem to play a special role in face processing^(page 8). Thus, we may expect that the self-face may rely on different processes when compared to a famous face (and unknown faces) but may be characterized by a robust mental representation such as other familiar faces, since the self-face is a familiar face as well.…”
Section: Discussionmentioning
confidence: 99%
“…Face-to-face encounters require responding and entering a relationship (which does not occur with famous people). Relationships with relatives involve the self, and familiar faces are embodied stimuli with meaning that include the self ( 27 ). The anomalies of “self-experience” are known to be specific to schizophrenia ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been shown that familiar faces are processed differently than faces of unknown people, due to different visual representations stored in memory, personal knowledge, and personal relevance ( 31 ). Furthermore, “familiarity” in the context of social rewards has multi-faceted meanings and there may be qualitative differences between familiarity with relatives, celebrities, and experimentally learned individuals ( 31 ), which can potentially lead to inconsistencies through differential engagement in experimental tasks ( 32 ). Altogether, familiarity may modulate social and non-social rewards differently, which should be considered in study designs.…”
Section: Dimensions Of Rewarding Stimulimentioning
confidence: 99%